The structure and properties of a hypoeutectic silumin subjected to complex electron–ion-plasma processing - Ivanov, Yu.F.; Gromov, V.E.; Zagulyaev, D.V.; Konovalov, S.V.; Rubannikova, Yu.A.; Semin, A.P. (Успехи физики металлов, 2019)
The layer-by-layer analysis of structural–phase states and tribological properties of hypoeutectic АК10М2Н-type silumin at the depth up to 170 μm after the complex processing is carried out by the state-of-the-art methods of physical materials science. It involves the electroexplosion alloying with titanium and yttrium-oxide powder in different ratios followed by electron-beam processing.